2020
DOI: 10.1016/j.toxrep.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Welding fume inhalation exposure and high-fat diet change lipid homeostasis in rat liver

Abstract: It is estimated that greater than 1 million workers are exposed to welding fume (WF) by inhalation daily. The potentially toxic metals found in WF are known to cause multiple adverse pulmonary and systemic effects, including cardiovascular disease, and these metals have also been shown to translocate to the liver. This occupational exposure combined with a high fat (HF) Western diet, which has been shown to cause hyperlipidemia and non-alcoholic fatty liver disease (NAFLD), has the potential to cause significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This study showed that the combined effects of welding fume inhalation and a high-fat diet significantly altered the hepatic lipidome and researchers found higher abundance of ceramide-1-phosphate in the regular diet welding fume-exposed group which has been shown to regulate the eicosanoid pathway involved in pro-inflammatory response. 25 Thus, our study is the first study focused on the longitudinal association between metabolic profile and inflammatory biomarkers in a working population. The knowledge generated from this study can be generalized to broader active working population.…”
Section: Discussionmentioning
confidence: 98%
“…This study showed that the combined effects of welding fume inhalation and a high-fat diet significantly altered the hepatic lipidome and researchers found higher abundance of ceramide-1-phosphate in the regular diet welding fume-exposed group which has been shown to regulate the eicosanoid pathway involved in pro-inflammatory response. 25 Thus, our study is the first study focused on the longitudinal association between metabolic profile and inflammatory biomarkers in a working population. The knowledge generated from this study can be generalized to broader active working population.…”
Section: Discussionmentioning
confidence: 98%
“…Further associations between diet and occupational-exposure related toxicity have been shown in animal studies. Rats fed a HFWD and exposed to occupational welding fumes developed increased kidney toxicity, altered serum enzyme and protein levels [11] , [12] , and the hepatic lipidome was altered [12] , compared to animals fed a standard diet (STD).…”
Section: Introductionmentioning
confidence: 99%
“…Boyce G. R. et al showed that the combined effects of welding fume inhalation and a high fat Western diet significantly altered the hepatic lipidome. Additionally, pulmonary exposure to welding fume alone increased lipid markers of inflammation [ 5 ]. Tsoukalas D. et al found that urine organic acid levels related to the mechanisms of energy production and detoxification were associated with the presence of autoimmune diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%